Quantifying Federal Regulatory Burdens in the Beer Value Chain. Issue 3 (17th March 2017) - Malone, Trey; Chambers, Dustin
Abstract: While the literature has discussed the impacts of specific regulations in the broader marketplace, nothing has been published that identifies the total number of federal regulatory restrictions imposed upon an entire agribusiness value chain. This letter uses a dataset generated via machine learning methods to count the total number of federal regulations imposed on the beer value chain. We show that 94, 212 federal regulatory constraints influenced the beer value chained in 2012, with the majority of constraints being imposed at the brewery level. [EconLit citations: D04, I18, O12]